1986
DOI: 10.1007/bf00139751
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of CO2-induced climatic change on water resources in the Great Lakes Basin

Abstract: Scenarios of CO2-induced climatic change, based on models produced by the Goddard Institute for Space Studies (GISS) and the Geophysical Fluid Dynamics Lab (GFDL), were used to estimate future changes in water supply in the Great Lakes Basin. The major components of annual Net Basin Supply, surface runoff and lake evaporation, were estimated using the Thornthwaite water balance model and the mass transfer approach, respectively. Two scenarios were derived from each climatic change model, one based on present n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 9 publications
2
65
1
3
Order By: Relevance
“…Différents modèles de circulation générale ont été utilisés jusqu'à maintenant dans les études hydrologiques nord-américaines mentionnées précé-demment (COHEN, 1986 ;CROLEY et HARTMANN, 1989). En particulier, pour les études sur les Grands Lacs du Bouclier canadien, les résultats du modèle GISS du * Goddar Institute for Space Science » avec une résolution horizontale de 8° x 10° (latitude-longitude) et du modèle GFDL du « Geophysica!…”
Section: Matériel Et Méthodes Les Modèles De Circulation Générale (Mcg)unclassified
See 1 more Smart Citation
“…Différents modèles de circulation générale ont été utilisés jusqu'à maintenant dans les études hydrologiques nord-américaines mentionnées précé-demment (COHEN, 1986 ;CROLEY et HARTMANN, 1989). En particulier, pour les études sur les Grands Lacs du Bouclier canadien, les résultats du modèle GISS du * Goddar Institute for Space Science » avec une résolution horizontale de 8° x 10° (latitude-longitude) et du modèle GFDL du « Geophysica!…”
Section: Matériel Et Méthodes Les Modèles De Circulation Générale (Mcg)unclassified
“…Ces méthodes ont été appliquées récemment avec succès au bassin des Grands Lacs du Bouclier canadien (COHEN, 1986(COHEN, , 1987CROLEY, 1990;HARTMANN, 1990 ;CROLEY et HARTMANN, 1989). Cependant la faible résolution spatiale des MCG utilisés limitait l'application de telles méthodes à des bassins de grandes dimensions.…”
Section: Introductionunclassified
“…The next generation of analyses (e.g. Rosenzweig 1985, Cohen 1986) used month-by-month or season-by-season simulations of climate from general circulation models (GCMs) for various points or gridcells on the surface of the earth. Most recently, analyses such as that of Wilks (1988) have used weather-generating techniques to produce realistic scenarios of daily weather series from the temporally aggregated GCM output that is made available for climate impact studies.…”
Section: Approaches To Examining Consequencesmentioning
confidence: 99%
“…Without a truly coordinated national or international program in climate impact assessment, most of the studies have focused on particular aspects of individual resource sectors in individual regions (e.g. Blasing & Solomon 1984, Rosenzweig 1985, Cohen 1986, Gleick 1987a, Miller et al 1987, Pastor & Post 1988. These sectoral studies are described in Section 2.…”
Section: Approaches To Examining Consequencesmentioning
confidence: 99%
“…Specifically, in the Great Lakes Basin, both empirical and aerodynamic techniques have been used to estimate evaporation, and studies conducted by Cohen (1986Cohen ( , 1990, Sanderson (1987), and Croley (1990Croley ( , 2004 have found that evaporation would be significantly increased under climate change scenarios. Sanderson andSmith (1990, 1993) used the Thornthwaite model and Smith and McBean (1993) used the HELP model and predicted twenty to thirty percent increases in potential evaporation and approximately a 15% increase in actual evaporation to occur.…”
Section: Assessment Of Historical Trendsmentioning
confidence: 99%